Freshwater fishes assemblages in stream and river of Malaysia - Tze N. Cheok; Soo Chen Lin (Faculty of Science and Natural Resources, 2021)
Ichthyofaunal study in Malaysia that mostly focused on one area and the lack of study interest make it difficult to overview the fish assemblages in Malaysia. Thus, a desktop study on the freshwater fish in streams and rivers of Malaysia was conducted with the aims to determine the current freshwater fish composition and assemblages in Malaysia. The desktop study was conducted with the main scientific databases including ScienceDirect, Scopus, Google Scholar, and Springer for relevant literature and data extraction. A total of 92 literatures from 11 states, together with 452 freshwater fish species from 49 families have been collected and recorded. Family Cyprinidae (115) had the highest number of species in Malaysia, followed by Danionidae (44), Bagridae (32), and Balithoridae (26). Interestingly, fish assemblages are found similar in Kelantan, Pahang, Perak, and Johor whereas demonstrated great dissimilarity in Sabah, Penang, Terengganu, and Selangor. This study revealed that the research on ichthyofaunal is inadequate in several states of Malaysia. More studies should be conducted in those states to fill in the research gap and provide knowledge and latest update on the ichthyofaunal study in Malaysia.